Comparing black deaths in custody, police brutality, and social justice solutions - Simmons, Janelle Christine (Advances in criminology, crime justice, and penology (ACCJP) book series, 2023)
"This book addresses the topic of Black Deaths in Custody which describes actions that lead to the death of Black people while they are in the process of being detained by a law enforcement agent or were already detained, focusing on three core countries where Black Deaths in Custody appear to occur at higher rates"--